Tradisi Maapam sebagai Sumber Inspirasi Penciptaan Motif Batik - Julia Dwi Sasmita; Riswel Zam (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
Maapam tradition is an annual tradition of the West Pasaman community, held during the month of rajab through the collective preparation of apam as an expression of gratitude, charity, and to welcome the holy month of ramadhan. This tradition carries both religious and social values, reflecting togetherness and communal activities passed down through generations. However, these local wisdom values have rarely been translated into textile craftworks, as maapam has traditionally been known merely as an annual activity without visual forms or physical symbols that signify or represent it as a cultural heritage. Therefore, the creation of batik motifs becomes an effort to present symbolic visual forms, document its values, and strengthen cultural identity so that it is more easily recognized and transmitted to future generations. This creative research aims to design motifs derived from the values and meanings of the maapam tradition through stylization, as well as to realize these motifs on long cloth using the hand-drawn batik technique. The method applied refers to the craft art creation process, consisting of the stages of exploration, design, realization, and presentation. The result is hand-drawn batik cloth representing the values of gratitude, togetherness, sharing, and mutual cooperation in the maapam tradition. The systematic application of this method produces batik works that are not only aesthetically valuable but also deeply meaningful as a form of preserving local traditions